Interest in Learning of Indonesian Students with Online Gaming Addiction In The Academic Learning Process - Fahrizal, Yanuar; Faiga, Nurul (Media Keperawatan Indonesia, 2021)
Student interest in learning has been declining due to the increasing number of distractions. Interest is one of the important factors contributing to one’s desire and motivation to satisfy curiosity. As the times evolve, many things affect student interest in learning; one of which is smartphones equipped with the internet that promotes the ease of performing activities. Smartphones and the internet offer online games that can be accessed by anyone to play at any time, which can trigger online gaming addiction. The study aims to examine the interest in learning of nursing students who are addicted to online games. This study employed a qualitative method with a phenomenological approach. Data were collected through interviews, observations and documentation. The participants of the study were five students recruited using a snowball sampling method. Data were analyzed using Giorgi method. Results showed that interest in learning of students with online gaming addiction in the academic learning process varies. This can be seen through three emerging themes: student gaming behaviour, changes in students after online gaming, and the learning process of students with addiction to online games. It can be concluded that students’ online game behaviour is influenced by impulsivity that changes student behaviour and leads to addiction.